(untitled) (University of Khartoum Engineering Journal, 2022)
Directing the transmit power towards the intended receiver reduces the required transmit power, reduces interference and increases the capacity. Current smart antennas use large arrays and complicated feeding networks rendering them impractical for small terminals. In this paper we design and analyse a 4 elements smart antenna array for terminals. The pattern is controlled by switching elements ON or OFF. Matlab and Micro-stripes models were used to analyse the design and the results showed the array can scan the beam in steps of 45°. A matching network was also designed to match the array to a 50W transmission line.